Microbial signatures in head and neck squamous cell carcinoma: an in silico study - Loganathan KAVITHA; Manogaran KUZHALMOZHI; Jayaseelan VIJAYASHREE PRIYADHARSINI; Arunachalam ARUN KUMAR; Krishna Mohan Rao UMADEVI; Kannan RANGANATHAN (Journal of Applied Oral Science)
Abstract Objectives The oral cavity harbors a plethora of bacterial species. Dysbiosis of oral and gut microbiota is associated with several oral and systemic pathologies, such as cancer, obesity, diabetes, atherosclerosis and gastrointestinal diseases. Imbalance in the oral-gut microbial axis has been associated with head and neck squamous cell carcinoma (HNSCC). This study aims to analyze the bacterial profile of HNSCC across various taxonomic units, investigate molecular patterns associated with prevalent bacterial phylum in HNSCC, and compare the bacterial profile in HNSCC and gastrointestinal (GI) carcinoma using computational analysis. Methodology The microbe-host transcriptomic, proteomic, and epigenetic analyses of HNSCC and GI carcinomas were performed using The Cancer Microbiome Atlas (TCMA) database. The differential expression of the host’s mRNA transcripts and proteins associated with tumor microbiome were analyzed using The University of Alabama at Birmingham Cancer data analysis (UALCAN) and Clinical Proteomic Tumor Analysis Consortium (CPTAC) websites. Results A decrease in Actinobacteria and an enrichment of Flavobacteria at the class level, Neisseriales, Pasteurellales, and Campylobacterales at the order level, Pasteurellaceae, Flavobacteriaceae, Campylobacteraceae, and Peptoniphilaceae at the family level, and Hemophilus, Porphyromonas, and Leptotrichia at the genus level were observed in HNSCC compared to the normal mucosa. RICTOR protein, mRNA transcripts (HIST1H2BB, SCARNA11, TBC1D21 gene), and hsa-miR-200a-5p miRNA were significantly correlated with prevalent bacterial species in HNSCC. A major increase in Actinobacteria, Fusobacteria, and Spirochaetes was observed in HNSCC compared to GI carcinoma. Conclusion The oral-gut microbial dysbiosis, as reflected by the differential abundance of bacterial species in oral and GI carcinomas, suggests the implication of tumor microbiome and their genomic interactions with the host in carcinogenesis.